Prayers of the Antediluvian Patriarchs: Revisiting the Form and Function of 4Q369 Prayer of Enosh - Pannkuk, Justin L. (Dead Sea discoveries, 2017)
This article reassesses the evidence for determining the form of 4Q369 “Prayer of Enosh” and, in light of this assessment, considers how the composition could function rhetorically. Based on textual and comparative literary evidence, the article proposes that the extant text is structured by a genealogical framework (1 i 9–10) in which historically-oriented prayers are attributed to specific patriarchal figures like Enosh (1 i 1–7) and Enoch or one of his near descendants (1 ii 1–12). These formal aspects of the composition are seen to have important rhetorical consequences: they position the implied audience as a third party between God and the esteemed figures from the remote past and they frame the prayers as accurate forecasts of salvation history. Together these features provide grounds upon which pious readers could have confidence in the inevitability of God’s fidelity until the eschaton.